Adrenomedullin: a vasodilator to treat sepsis? - Pugin, Jérôme (BioMed Central, 2014)
Adrenomedullin is a vasodilatory polypeptide with pleiotropic effects secreted by various organs. Adrenomedullin is produced first as a prepropeptide, and then cleaved into mature adrenomedullin and mid-regional proadrenomedullin. Whereas levels of the latter have been shown to correlate with severity of sepsis and carry prognostic value, adrenomedullin plays a role in vascular tone homeostasis. In the previous issue of Critical Care, the infusion of exogenous adrenomedullin is suggested to protect against increased lung endothelial permeability and end-organ dysfunction in a model of pneumococcal pneumonia in mechanically ventilated mice, possibly by stabilizing vascular endothelia. Since adrenomedullin is a strong vasodilatory molecule, further studies are needed to evaluate its potential as a future treatment of sepsis.